Mathematical Problem Solving Ability on Problem Based Learning Assisted by GeoGebra in Primary School - Kurniawati, Ike; Joko Raharjo, Tri; Khumaedi, Khumaedi (Educational Management, 2021)
Training students through problem solving in mathematics learning is expected to be able to equip them to solve existing problems easily in everyday life. This study aims to analyse the use of Problem Based Learning (PBL) model assisted by GeoGebra in improving students' mathematical problem solving abilities. The method of this study was quantitative experimental type using Pre-Test Post-Test in one group. The samples of the study were students of VA class from SDN Petompon 01 and students of VA class from SDN Sampangan 02 with a total of 64 students. The data were obtained through the question sheet of problem solving abilities. Then, the data were analysed using N-gain. After carrying out learning using PBL models assisted by GeoGebra, the final results showed that mathematical problem solving ability from both groups of students experienced an average increase of 0.55 with a medium category. Therefore, students need to get more learning and practice in solving the questions using problem solving. Because problem solving abilities will be more optimal if the students are given the opportunity to learn with the real world directly.